ANALISIS SISTEM PENGELOLAAN PENGADUAN MASYARAKAT PADA PUSAT PENGELOLAAN PENGADUAN MASYARAKAT (P3M) KOTA SEMARANG - Ayuningtyas Dyah Pitaloka Subagyo; Herbasuki Nurcahyanto; Aufarul Marom (Journal of Public Policy and Management Review, 2023)
As a form of response to the need for complaint management in the City of Semarang through Semarang Mayor Regulation Number 34 of 2017, a community complaint unit was formed which became known as the "Community Complaint Management Center (P3M)".The purpose of this research is to analyze the P3M system in Semarang City and its supporting and inhibiting factors. This research uses a qualitative descriptive research type.This research in conducting an analysis using the theory of management information systems by looking at management aspects (input, process, output, and feedback). The informant determination technique used in this study was snowball sampling with data collection methods through interviews, observation, and documentation.The results of this study indicate that the public complaint management system at P3M Semarang City is in accordance with the complaint management system both based on P3M regulations and the literature regarding complaint management. The public complaint management system at P3M Semarang City is seen through management aspects consisting of input, process, output, and feedback which have handled various complaints from the public even though there are still some problems in each of these aspects. The public complaints management system at P3M Semarang City has supporting factors including infrastructure and socialization and inhibiting factors including publications and potential human resources. To overcome these problems, it is necessary to have periodic monitoring and evaluation from the government to assist the implementation of public complaint management at P3M Semarang City so that problems and needs can be accommodated in accordance with the provisions of Semarang mayor regulation number 34 of 2017.